PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL DAN BUDAYA ORGANISASI TERHADAP KEPUASAN KERHA PERAWAT PADA RS. IBNU SINA PEKANBARU - Afria Nesti; Kasmiruddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This Study aimed to describe the influence of leadership style transformational and organizational culture to job satisfaction at the RSI Ibnu Sina Pekanbaru. Leadership style transformational as variable (X1), organizational culture as variabel (X2), and job satisfaction as variabel (Y). The menthod in this research is descriptive and quntitative using SPSS 21, Where the sample use are 68 nurses performed by proposional sampling method and data collection technique through questionnaires.From the results of the data analysis that includes a test of validity, reability, determination test, simple linear regression, multiple linear regression, test t, and test f.So it can be concluded that leadership style transformational has significant effect on job satisfaction on RS Ibnu Sina Pekanbaru, organizational culture has significant effect on job satisfaction on nurse RS Ibnu Sina Pekanbaru, leadership style transformational and organizational culture have significant effect to job satisfaction on nurse RSI Ibnu Sina PekanbaruKeyword: Leadership Style Transformational, Organizational Culture, and Job Satisfaction